Quantifying the impact of variable BLR diffuse continuum contributions on measured continuum interband delays. Issue 4 (23rd August 2019) - Korista, K T; Goad, M R
ABSTRACT: We investigate the contribution of reprocessed continuum emission (1000–10 000 Å) originating in broad-line region (BLR) gas, the diffuse continuum (DC), to the wavelength-dependent continuum delays measured in AGN disc reverberation mapping experiments. Assuming a spherical BLR geometry, we adopt a Local Optimally emitting Cloud (LOC) model for the BLR that approximately reproduces the broad emission-line strengths of the strongest UV lines (Ly α and C iv ) in NGC 5548. Within this LOC framework, we explore how assumptions about the gas hydrogen density and column density distributions influence flux and delay spectra of the DC. We find that: (i) models which match well measured emission-line luminosities and time delays also produce a significant DC component, (ii) increased n_H and/or N_H, particularly at smaller BLR radii, result in larger DC luminosities and reduced DC delays, (iii) in a given continuum band the relative importance of the DC component to the measured interband delays is proportional (though not 1:1) to its fractional contribution to the total light in that band, (iv) the measured DC delays and DC variability amplitude depend also on the variability amplitude and characteristic variability time-scale of the driving continuum, (v) the DC radial surface emissivity distributions F ( r ) approximate power laws in radius with indices close to −2 (≈1:1 response to variations in the driving continuum flux), thus their physics is relatively simple and less sensitive to the unknown geometry and uncertainties in radiative transfer. Finally, we provide a simple recipe for estimating the DC contribution in disc reverberation mapping experiments.